STRATEGI TRANSISI DARI PERTANIAN KONVENSIONAL KE SISTEM ORGANIK PADA PERTANIAN SAYURAN DI KECAMATAN BATURITI, KABUPATEN TABANAN, BALI. - Sardiana, I Ketut (Bumi Lestari; Vol 17 No 1 (2017), 2017)
Increased consumer awareness of safe vegetable products free of chemical residues and environmentally friendly has encouraged the development of organic farming. However, significant reduction in crop yields in the early phase of the application of organic farming has hindered the development of the system.This study aims to determine the combination of manure and NPK fertilizer that provides vegetables yields no different from conventional farming in order to determine the strategy of transition from conventional farming to organic systems..The study was conducted in Bangli  village, Baturiti district,  Tabanan regency, Bali. A randomized completely block design was used in this experiment with six  treatments of combination manurewith NPK fertilyzer and three replications. As an indicator plant is caisim( Brassica Chinensis L). The results showed that the application  of  manure 20 tons ha 1   (organic farming)resulted in the growth and yields of caisim are significantly lower than conventional systems(100 % of NPK dosage). Meanwhile, theapplication of 10 tons ha manure combined with a 50% of NPK fertilizer dosage to produce caisin are not significantly differentwith conventional farming, and soil properties such as organic C, total-N, available P, and exchangeable K no different  with an organic farming system.Thus, this treatment can be used as a transition strategy from conventional farming to organic systems